Tetragonal phase BaZrxTi1-xO3 ceramic self-cleaning film and preparation method thereof
By preparing the tetragonal BaZrxTi1-xO3 ceramic self-cleaning membrane, the problem of membrane pore blockage in membrane separation technology is solved, efficient water flux and filtration performance are achieved, the cost of use is reduced, and the drawbacks of traditional cleaning methods are avoided.
Patent Information
- Application Number
- CN202510319937.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The problem of membrane pore blockage in membrane separation technology leads to a decrease in water flux, a decrease in filtration performance and an increase in usage costs. The existing cleaning methods have structural damage and secondary pollution, and cannot effectively solve the problem of membrane pore blockage in complex and diverse pollutants.
The preparation method of the tetragonal phase BaZrxTi1-xO3 ceramic self-cleaning film is adopted. By preparing chelating agent, barium salt, titanium salt and alkaline solution, forming a barium zirconium titanate precursor solution, rotary evaporation reaction to prepare powder, and molding the ceramic film through a tablet press to realize the preparation of the ceramic self-cleaning film.
The prepared tetragonal BaZrxTi1-xO3 ceramic self-cleaning membrane has high water flux, smooth surface, good hydrophilicity, excellent self-cleaning effect, and meets the requirements of mechanical properties, which can effectively prevent membrane pores, improve filtration performance, and reduce usage costs.
Smart Images

Figure CN119951348A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane separation and specifically relates to a tetragonal BaZr x Ti 1-x O3 ceramic self-cleaning membrane and preparation method thereof. Background Art
[0002] In the context of the global efforts to promote green development, the problem of wastewater treatment has become the focus of attention of countries around the world. In response to the problem of sewage treatment, a variety of methods have been explored, including light and sound catalysts, distillation, advanced oxidation processes, electrocoagulation, adsorption and membrane separation technologies, but in the actual development process, many technical methods are constrained by reality and cannot be popularized. The advanced membrane separation technology designed and improved since the 1960s has emerged as an economical, efficient and scalable solution. Although membrane separation technology has the advantages of economic efficiency, there are still some problems. The biggest problem in membrane separation technology is the problem of membrane pore blockage, that is, the deposition of pollutants on the membrane surface and in the pores, which will eventually lead to a decrease in water flux, reduced filtration performance and increased use costs. In response to the problem of membrane pore blockage, methods such as backwashing and chemical cleaning have been used, but although these methods can temporarily restore the filtration and anti-fouling performance of the membrane, they all have some disadvantages. Backwashing can cause structural damage to the membrane and increase economic consumption, and chemical cleaning can cause secondary pollution of chemical reagents. For the complex and diverse pollutant systems in the current era, as well as the problem of membrane pore blockage, static membranes can no longer play their ideal role to achieve the purpose of economic efficiency. At this time, the development of functional membranes with self-cleaning capabilities has become the focus of solving the problem. Summary of the invention
[0003] In view of the membrane fouling problem existing in membrane separation technology, the present invention provides a tetragonal BaZr x Ti 1-x The invention discloses a method for preparing a self-cleaning ceramic membrane having a high water flux, a smooth surface, good hydrophilicity, excellent self-cleaning effect, and mechanical properties that meet the requirements. x Ti 1-x O3 ceramic self-cleaning membrane. The present invention solves the problem of anti-fouling membrane pore blockage and improves its filtration performance. The preparation method is simple and easy to implement and suitable for large-scale production. The prepared tetragonal BaZr x Ti 1- x O3 ceramic self-cleaning membrane is a promising membrane for sewage pollution treatment.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A tetragonal BaZr x Ti 1-xThe preparation method of O3 ceramic self-cleaning membrane specifically comprises the following steps:
[0006] Step 1, prepare chelating agent solution
[0007] Weigh a chelating agent and dissolve it in deionized water, stirring until it is completely dissolved to obtain a chelating agent solution;
[0008] Step 2: Prepare barium salt solution
[0009] Weigh BaCl2 and dissolve it in deionized water, stirring until it is completely dissolved to obtain a colorless barium salt solution system;
[0010] Step 3, prepare titanium salt solution
[0011] Weigh C 16 H 36 O4Ti was dissolved in anhydrous ethanol and stirred evenly to obtain a colorless titanium salt solution system;
[0012] Step 4: Prepare alkaline solution
[0013] Weigh KOH and dissolve it in deionized water and stir evenly until the KOH particles are completely dissolved to obtain a colorless alkaline solution;
[0014] Step 5: Prepare barium titanate precursor solution
[0015] Slowly adding the chelating agent solution prepared in step 1 and the barium salt solution prepared in step 2 to the titanium salt solution prepared in step 3, stirring evenly to form a mixed solution system, then adding the alkaline solution prepared in step 4 to the mixed solution system, and finally reacting under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, thereby obtaining a BaTiO3 precursor solution;
[0016] Step 6: Prepare barium zirconate titanate precursor solution
[0017] Add ZrO2 powder to the BaTiO3 precursor solution prepared in step 5 and stir evenly to obtain BaZr x Ti 1-x O3 precursor solution;
[0018] Step 7, preparation of BaZr x Ti 1-x O3 powder
[0019] The BaZr prepared in step 6 x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, and the obtained white precipitate was centrifuged and dried to obtain BaZr x Ti 1-x O3 precursor powder; BaZr x Ti 1-xThe O3 precursor powder was placed in an air furnace and calcined at high temperature to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0020] Step 8: Prepare film-forming solution
[0021] Weigh a film-forming agent and dissolve it in deionized water, stirring evenly to obtain a film-forming agent solution;
[0022] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane
[0023] Weigh the tetragonal BaZr prepared in step 7 x Ti 1-x O3 powder is placed in a mortar, and the film-forming agent solution prepared in step 8 is dripped into it. After being ground evenly, it is added to a pressure mold, and a tablet press is used to form a ceramic film blank; the obtained ceramic blank is placed in an air furnace and calcined at high temperature to obtain a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0024] Furthermore, a magnetic stirrer is used in the stirring process in step 1, step 2, step 3, step 4, step 5, step 6 and step 8.
[0025] Furthermore, the chelating agent in step 1 is ethanolamine.
[0026] Furthermore, the ZrO2 powder in step 6 is tetragonal nanoparticles.
[0027] Further, the rotary evaporation reaction process in step 7 consists of two stages. The reaction conditions of the first stage are: water bath temperature 50°C-60°C, rotary evaporator pressure 142mbar-146mbar, time 30min-60min; the reaction conditions of the second stage are: water bath temperature 60°C-70°C, rotary evaporator pressure 72mbar-76mbar, time 90min-120min; the centrifugation process includes three water washes and three alcohol washes; the drying conditions are: the white precipitate is dried in an oven, the drying temperature is 60°C-100°C, and the drying time is 12h-36h; BaZr x Ti 1-x The high temperature calcination temperature of O3 precursor powder is 800℃-1200℃, and the high temperature calcination time is 1h-4h.
[0028] Furthermore, the film-forming agent in step 8 is any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, propylene glycol, and glycerol.
[0029] Furthermore, in step 9, the pressing pressure of the ceramic membrane green body formed by the tablet press is 8Mpa-15Mpa, the holding time is 60s-180s, the high-temperature calcination temperature is 1200℃-1400℃, and the high-temperature calcination time is 1h-4h.
[0030] According to the above-mentioned tetragonal BaZr x Ti 1-x Preparation method of O3 ceramic self-cleaning membrane prepared by tetragonal BaZr x Ti 1-x O3 ceramic self-cleaning membrane.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The raw materials used in the present invention are cheap, readily available, green and pollution-free reagents. The designed synthesis method uses a rotary evaporation device that can be scaled up from experimental to industrial levels to prepare powders, which is conducive to mass production, has good process stability, is suitable for industrial production, and can promote the commercialization of high-performance ceramic materials.
[0033] (2) The present invention prepares ceramic self-cleaning membranes by a traditional dry pressing and sintering method, which is simple and easy to operate, has strong repeatability, and is compatible with the production lines of most ceramic companies. x Ti 1-x The O3 ceramic self-cleaning membrane has low cost, better sewage self-cleaning effect than existing commercial products, and is economical and practical. It can promote the commercialization of high-performance ceramic self-cleaning membranes in sewage treatment.
[0034] (3) The tetragonal BaZr prepared by the present invention x Ti 1-x The O3 ceramic self-cleaning membrane has uniform pore size distribution, smooth surface, strong hydrophilicity, and good piezoelectricity, which can achieve efficient self-cleaning. It can still maintain high water flux in pollutant solutions, meeting the requirements of an excellent anti-fouling surface.
[0035] (4) The tetragonal BaZr prepared by the present invention x Ti 1-x O3 ceramic self-cleaning membrane has good mechanical properties and no longer requires traditional support to meet the mechanical performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A tetragonal BaZr provided by the present invention x Ti 1-x Process flow chart of the preparation method of O3 ceramic self-cleaning membrane.
[0037] Figure 2The tetragonal BaZr prepared in Example 1 of the present invention x Ti 1-x Schematic diagram of XRD pattern of O3 ceramic self-cleaning membrane;
[0038] Figure 3 The tetragonal BaZr prepared in Example 2 of the present invention x Ti 1-x SEM diagram of O3 ceramic self-cleaning membrane;
[0039] Figure 4 The tetragonal BaZr prepared in Example 3 of the present invention x Ti 1-x Schematic diagram of the two-dimensional and three-dimensional morphology of O3 ceramic self-cleaning membrane;
[0040] Figure 5 The tetragonal BaZr prepared in Example 3 of the present invention x Ti 1-x Schematic diagram of elastic modulus of O3 ceramic self-cleaning membrane;
[0041] Figure 6 The tetragonal BaZr prepared in Example 3 of the present invention x Ti 1-x Schematic diagram of the hydrophilic angle of O3 ceramic self-cleaning membrane;
[0042] Figure 7 The tetragonal BaZr prepared in Example 5 of the present invention x Ti 1-x Macroscopic filtration experiment diagram of O3 ceramic self-cleaning membrane;
[0043] Figure 8 The tetragonal BaZr prepared in Example 3 of the present invention x Ti 1-x Schematic diagram of water flux in BSA-contaminated liquid of O3 ceramic self-cleaning membrane. DETAILED DESCRIPTION
[0044] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0045] like Figure 1 As shown, the present invention provides a tetragonal BaZr x Ti 1-x The preparation method of O3 ceramic self-cleaning membrane specifically comprises the following steps:
[0046] Step 1, preparing a chelating agent solution, weighing 0.05 mol-0.25 mol of a chelating agent (ethanolamine) and dissolving it in 50 mL-250 mL of deionized water, stirring with a magnetic stirrer for 10 min-60 min until it is completely dissolved to obtain a chelating agent solution;
[0047] Step 2, prepare a barium salt solution, weigh 0.05mol-0.25mol BaCl2 and dissolve it in 50mL-250mL deionized water, use a magnetic stirrer to stir for 10min-60min, and stir until it is completely dissolved to obtain a colorless barium salt solution system;
[0048] Step 3, prepare titanium salt solution, weigh 0.04mol-0.25mol C 16 H 36 O4Ti is dissolved in 30mL-150mL of anhydrous ethanol and stirred with a magnetic stirrer for 10min-60min to obtain a colorless titanium salt solution system;
[0049] Step 4, prepare an alkaline solution, weigh 0.3 mol-0.7 mol KOH and dissolve it in 50 mL-100 mL deionized water, and stir it with a magnetic stirrer for 10 min-60 min until the KOH particles are completely dissolved to obtain a colorless alkaline solution;
[0050] Step 5, preparing a barium titanate precursor solution, slowly adding the chelating agent solution and the barium salt solution to the titanium salt solution, stirring with a magnetic stirrer for 10 min-60 min, stirring evenly to form a mixed solution system, then adding the alkaline solution to the mixed solution system, and finally reacting under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, thereby obtaining a BaTiO3 precursor solution;
[0051] Step 6: prepare a barium zirconate titanate precursor solution, add 0.001 mol-0.03 mol of ZrO2 powder (tetragonal nanoparticles) to the BaTiO3 precursor solution, stir for 10 min-60 min using a magnetic stirrer, and stir evenly to obtain BaZr x Ti 1-x O3 precursor solution;
[0052] Step 7, Preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-xThe O3 precursor solution is poured into an eggplant-shaped bottle for rotary evaporation reaction. The rotary evaporation reaction process consists of two stages. The reaction conditions of the first stage are: water bath temperature 50℃-60℃, rotary evaporator pressure 142mbar-146mbar, time 30min-60min; the reaction conditions of the second stage are: water bath temperature 60℃-70℃, rotary evaporator pressure 72mbar-76mbar, time 90min-120min; after the rotary evaporation reaction, the obtained white precipitate is centrifuged and dried, and the centrifugation process includes three water washes and three alcohol washes; the drying conditions are: the white precipitate is dried in an oven, the drying temperature is 60℃-100℃, and the drying time is 12h-36h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace for high temperature calcination, the high temperature calcination temperature is 800℃-1200℃, the high temperature calcination time is 1h-4h, and the tetragonal BaZr is obtained after high temperature calcination x Ti 1-x O3 powder;
[0053] Step 8, preparing a film-forming agent solution, weighing a film-forming agent and dissolving it in deionized water, stirring with a magnetic stirrer for 10 min-60 min, and stirring evenly to obtain a film-forming agent solution; the film-forming agent is any one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), propylene glycol, and glycerol, and the mass fraction of the film-forming agent is 2wt%-8wt%;
[0054] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 0.5g-3.0g of tetragonal BaZr x Ti 1-x O3 powder is placed in a mortar, and the film-forming agent solution is dripped into it. After being ground evenly, it is added to a pressure mold, and a tablet press is used to form a ceramic film blank. The pressing pressure is 8Mpa-15Mpa, and the pressure holding time is 60s-180s. Then the obtained ceramic blank is placed in an air furnace for high-temperature calcination. The high-temperature calcination temperature is 1200℃-1400℃, and the high-temperature calcination time is 1h-4h. After high-temperature calcination, tetragonal BaZr x Ti 1-x O3 ceramics.
[0055] Example 1
[0056] Step 1, preparing a chelating agent solution, weighing 0.05 mol of ethanolamine and dissolving it in 50 mL of deionized water, stirring with a magnetic stirrer for 10 min to obtain a chelating agent solution;
[0057] Step 2, prepare a barium salt solution, weigh 0.05 mol BaCl2 and dissolve it in 50 mL deionized water, stir it with a magnetic stirrer for 10 minutes, and obtain a colorless barium salt solution system;
[0058] Step 3, prepare titanium salt solution, weigh 0.048 mol C 16 H 36 O4Ti was dissolved in 30 mL of anhydrous ethanol and stirred for 30 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0059] Step 4, prepare an alkaline solution, weigh 0.5 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0060] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 30 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, and obtain a BaTiO3 precursor solution.
[0061] Step 6: prepare a barium zirconate titanate precursor solution, weigh 0.002 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution, stir it with a magnetic stirrer for 60 min, and obtain BaZr x Ti 1-x O3 precursor solution.
[0062] Step 7, preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction. The parameters of the first stage were: water bath temperature 55°C, rotary evaporator pressure 142mbar, time 60min; the parameters of the second stage were: water bath temperature 65°C, rotary evaporator pressure 74mbar, time 120min. The obtained white precipitate was first washed 3 times with ultrapure water, then washed 3 times with anhydrous ethanol; finally, it was placed in a 60°C oven and dried for 24h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 1000°C for 2 hours to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0063] Step 8, preparing a film-forming agent solution, weighing 2 g of PVA and dissolving it in 100 mL of deionized water, stirring with a magnetic stirrer for 10 minutes to obtain a film-forming agent solution.
[0064] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 2g of tetragonal BaZr x Ti 1-x O3 powder was placed in a mortar, 4 mL of film-forming agent solution was dropped into it, and after being evenly ground, it was added into a pressure mold with a diameter of 25 mm, and the pressure was 10 MPa. The pressure was maintained for 90 seconds, and a tablet press was used to form a ceramic film blank. The obtained ceramic blank was placed in an air furnace for high-temperature calcination at a temperature of 1200 ° C and a holding time of 2 hours. After calcination, a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0065] Figure 2 The prepared tetragonal BaZr x Ti 1-x XRD pattern of O3 ceramic self-cleaning membrane. Tetragonal BaZr x Ti 1- x The O3 ceramic self-cleaning film is highly consistent with the standard card of tetragonal BaTiO3 (JCPDS NO:05-0626), and a clear characteristic peak of tetragonal BaTiO3 appears at 45°, which proves that the tetragonal BaZr x Ti 1-x O3, further magnification of the characteristic peak at 45° shows that the diffraction peak shifts significantly to the left after doping, proving the success of doping.
[0066] Example 2
[0067] Step 1, preparing a chelating agent solution, weighing 0.05 mol of ethanolamine and dissolving it in 50 mL of deionized water, stirring with a magnetic stirrer for 20 minutes to obtain a chelating agent solution;
[0068] Step 2, prepare a barium salt solution, weigh 0.05 mol BaCl2 and dissolve it in 50 mL deionized water, stir it with a magnetic stirrer for 20 minutes, and obtain a colorless barium salt solution system;
[0069] Step 3, prepare titanium salt solution, weigh 0.045 mol C 16 H 36 O4Ti was dissolved in 30 mL of anhydrous ethanol and stirred for 30 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0070] Step 4, prepare an alkaline solution, weigh 0.5 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0071] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 30 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, and obtain a BaTiO3 precursor solution.
[0072] Step 6: prepare a barium zirconate titanate precursor solution, weigh 0.005 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution, stir it with a magnetic stirrer for 45 minutes, and obtain BaZr x Ti 1-x O3 precursor solution.
[0073] Step 7, preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, with a water bath temperature of 50°C, a rotary evaporator pressure of 146 mbar, and a time of 60 min; the parameters for the second stage were: a water bath temperature of 60°C, a rotary evaporator pressure of 76 mbar, and a time of 120 min. The obtained white precipitate was first washed 3 times with ultrapure water, and then washed 3 times with anhydrous ethanol; finally, it was placed in an oven at 80°C and dried for 12 h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 900°C for 3 hours to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0074] Step 8, preparing a film-forming agent solution, weighing 2 g of PVP and dissolving it in 100 mL of deionized water, stirring it with a magnetic stirrer for 10 minutes to obtain a film-forming agent solution.
[0075] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 2g of tetragonal BaZr x Ti 1-xO3 powder was placed in a mortar, 4 mL of film-forming agent solution was dropped into it, and after being evenly ground, it was added into a pressure mold with a diameter of 25 mm, and the pressure was 15 MPa, and the pressure holding time was 90 s. A tablet press was used to form a ceramic film blank; the obtained ceramic blank was placed in an air furnace for high-temperature calcination at a calcination temperature of 1400 ° C and a holding time of 2 h. After calcination, a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0076] Figure 3 The prepared tetragonal BaZr x Ti 1-x SEM image of O3 ceramic self-cleaning membrane; Figure 3 (a) The magnification is 1k, and it can be seen that the surface is relatively dense. Figure 3 (b) Magnification is 10k.
[0077] Figure 3 (a) Tetragonal BaZr x Ti 1-x The surface of the O3 ceramic self-cleaning membrane is flat and smooth, with no obvious macropores. Figure 3 (b) shows that the gaps between particles are small, the particles tend to be connected to each other, the grain size is small, and the grain boundaries become blurred. Overall, the tetragonal BaZrxTi1-xO3 ceramic self-cleaning film is flat, dense, and defect-free.
[0078] Example 3
[0079] Step 1, preparing a chelating agent solution, weighing 0.05 mol of ethanolamine and dissolving it in 50 mL of deionized water, stirring with a magnetic stirrer for 30 minutes to obtain a chelating agent solution;
[0080] Step 2, prepare a barium salt solution, weigh 0.05 mol BaCl2 and dissolve it in 50 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless barium salt solution system;
[0081] Step 3, prepare titanium salt solution, weigh 0.042 mol C 16 H 36 O4Ti was dissolved in 30 mL of anhydrous ethanol and stirred for 30 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0082] Step 4, prepare an alkaline solution, weigh 0.6 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0083] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 30 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, and obtain a BaTiO3 precursor solution.
[0084] Step 6: prepare a barium zirconate titanate precursor solution, weigh 0.008 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution, stir it with a magnetic stirrer for 40 minutes, and obtain BaZr x Ti 1-x O3 precursor solution.
[0085] Step 7, preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, with a water bath temperature of 60°C, a rotary evaporator pressure of 142 mbar, and a time of 45 min. The parameters for the second stage were: a water bath temperature of 65°C, a rotary evaporator pressure of 72 mbar, and a time of 100 min. The obtained white precipitate was first washed 3 times with ultrapure water, and then washed 3 times with anhydrous ethanol; finally, it was placed in a 60°C oven and dried for 36 h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 800°C for 4 hours to obtain tetragonal BaZr x Ti 1- x O3 powder;
[0086] Step 8, preparing a film-forming agent solution, weighing 2 g of PEG and dissolving it in 100 mL of deionized water, stirring it with a magnetic stirrer for 10 minutes to obtain a film-forming agent solution.
[0087] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 2g of tetragonal BaZr x Ti 1-x O3 powder was placed in a mortar, 4 mL of film-forming agent solution was dropped into it, and after being evenly ground, it was added into a pressure mold with a diameter of 25 mm, and the pressure was 12 MPa, and the holding time was 100 s. A tablet press was used to form a ceramic film blank; the obtained ceramic blank was placed in an air furnace for high-temperature calcination at a calcination temperature of 1200 ° C and a holding time of 2 h. After calcination, a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0088] Figure 4 The tetragonal BaZr prepared in this example x Ti 1-x Two-dimensional and three-dimensional morphology of O3 ceramic self-cleaning membranes, tetragonal BaZr x Ti 1-x The two-dimensional and three-dimensional morphologies of the surface of the O3 ceramic self-cleaning membrane were observed. From the two-dimensional morphology, the tetragonal BaZr x Ti 1-x The surface of the O3 ceramic self-cleaning membrane is relatively dense, and there are no macroscopic cracks or defects. The color distribution of the three-dimensional morphology can be used to determine whether the sample surface is flat. It can be seen from the figure that BaZr x Ti 1-x The surface of the O3 ceramic self-cleaning membrane is smooth, and the surface roughness is 1.714 μm.
[0089] Figure 5 The tetragonal BaZr prepared in this example x Ti 1-x Schematic diagram of the elastic modulus of O3 ceramic self-cleaning membrane, for tetragonal BaZr x Ti 1-x The elastic modulus of O3 ceramic self-cleaning membrane was studied to explore its mechanical properties. The elastic modulus can reach 189.552MPa, which has excellent mechanical properties.
[0090] Figure 6 The tetragonal BaZr prepared in this example x Ti 1-x Schematic diagram of the hydrophilic angle of O3 ceramic self-cleaning membrane. It can be seen from the figure that the tetragonal BaZr x Ti 1-x The hydrophilic angle of the O3 ceramic self-cleaning membrane is 0°, and the material is completely wetted and has super hydrophilicity.
[0091] Figure 8 The tetragonal BaZr prepared in this example x Ti 1-x Schematic diagram of water flux in BSA contaminated liquid of O3 ceramic self-cleaning membrane, using three-plate ceramic membrane tester to measure tetragonal BaZr x Ti 1-x The water flux of O3 ceramic self-cleaning membrane in polluted liquid was tested to provide the tetragonal BaZr under pulse conditions. x Ti 1-x The water flux of the O3 ceramic self-cleaning membrane did not change significantly within 1 hour, and it could still maintain a high water flux. However, under constant pressure conditions, the flux dropped to 0 within 30 minutes, and it no longer had the membrane separation function. x Ti 1-xO3 ceramic self-cleaning membrane has good self-cleaning effect and can realize the treatment of pollutants.
[0092] Example 4
[0093] Step 1, preparing a chelating agent solution, weighing 0.1 mol of ethanolamine and dissolving it in 100 mL of deionized water, stirring with a magnetic stirrer for 10 minutes to obtain a chelating agent solution;
[0094] Step 2, prepare a barium salt solution, weigh 0.1 mol BaCl2 and dissolve it in 100 mL deionized water, stir it with a magnetic stirrer for 10 minutes, and obtain a colorless barium salt solution system;
[0095] Step 3, prepare titanium salt solution, weigh 0.09 mol C 16 H 36 O4Ti was dissolved in 60 mL of anhydrous ethanol and stirred for 30 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0096] Step 4, prepare an alkaline solution, weigh 0.4 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0097] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 30 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, and obtain a BaTiO3 precursor solution.
[0098] Step 6: prepare a barium zirconate titanate precursor solution, weigh 0.01 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution, stir it with a magnetic stirrer for 40 minutes, and obtain BaZr x Ti 1-x O3 precursor solution.
[0099] Step 7, Preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, with a water bath temperature of 60°C, a rotary evaporator pressure of 143 mbar, and a time of 50 min. The parameters for the second stage were: a water bath temperature of 70°C, a rotary evaporator pressure of 72 mbar, and a time of 90 min. The obtained white precipitate was first washed 3 times with ultrapure water, and then washed 3 times with anhydrous ethanol; finally, it was placed in a 60°C oven and dried for 24 h to obtain BaZr x Ti 1-xO3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 1100°C for 2 hours to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0100] Step 8, preparing a film-forming agent solution, weighing 3 g of PVP and dissolving it in 100 mL of deionized water, stirring it with a magnetic stirrer for 10 minutes to obtain a film-forming agent solution.
[0101] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 3g of tetragonal BaZr x Ti 1-x O3 powder was placed in a mortar, 5 mL of film-forming agent solution was dropped into it, and after being evenly ground, it was added into a pressure mold with a diameter of 25 mm, and the pressure was 8 MPa, and the holding time was 150 s. A tablet press was used to form a ceramic film blank; the obtained ceramic blank was placed in an air furnace for high-temperature calcination at a calcination temperature of 1200 ° C and a holding time of 2 h. After calcination, a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0102] Example 5
[0103] Step 1, preparing a chelating agent solution, weighing 0.15 mol of ethanolamine and dissolving it in 100 mL of deionized water, stirring with a magnetic stirrer for 15 minutes to obtain a chelating agent solution;
[0104] Step 2, prepare a barium salt solution, weigh 0.15 mol BaCl2 and dissolve it in 100 mL deionized water, stir it with a magnetic stirrer for 15 minutes, and obtain a colorless barium salt solution system;
[0105] Step 3, prepare titanium salt solution, weigh 0.144 mol C 16 H 36 O4Ti was dissolved in 100 mL of anhydrous ethanol and stirred for 15 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0106] Step 4, prepare an alkaline solution, weigh 0.7 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0107] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 45 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer to obtain a BaTiO3 precursor solution.
[0108] Step 6: Prepare a barium zirconate titanate precursor solution. Weigh 0.006 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution. Stir with a magnetic stirrer for 45 min to obtain BaZr x Ti 1-x O3 precursor solution.
[0109] Step 7, Preparation of BaZr x Ti 1-x O3 powder: BaZr x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, with a water bath temperature of 55°C, a rotary evaporator pressure of 144 mbar, and a time of 60 min; the parameters for the second stage were: a water bath temperature of 65°C, a rotary evaporator pressure of 72 mbar, and a time of 100 min. The obtained white precipitate was first washed 3 times with ultrapure water, and then washed 3 times with anhydrous ethanol; finally, it was placed in an oven at 100°C and dried for 12 h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 1200°C for 3 hours to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0110] Step 8, preparing a film-forming agent solution, weighing 8 g of propylene glycol and dissolving it in 100 mL of deionized water, stirring with a magnetic stirrer for 30 minutes to obtain a film-forming agent solution.
[0111] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 3g of tetragonal BaZr x Ti 1-x O3 powder was placed in a mortar, and 6 mL of film-forming agent solution was dropped into it. After being ground evenly, it was added into a pressure mold with a diameter of 25 mm. The pressure was 12 MPa and the holding time was 120 s. A tablet press was used to form a ceramic film blank. The obtained ceramic blank was placed in an air furnace for high-temperature calcination at a calcination temperature of 1400 ° C and a holding time of 1 h. After calcination, a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0112] Figure 7 The tetragonal BaZr prepared in this example x Ti 1-x Macroscopic filtration experiment of O3 ceramic self-cleaning membrane. x Ti 1-xThe O3 ceramic self-cleaning membrane filters the Oil Red O dye solution to test its filtering function. Through this macroscopic filtration experiment, the filtering conditions of the filter material on actual oily pollutants can be simulated. The Oil Red O dye solution is bright red, and the eye-catching color makes it possible to see the filtering effect at a macroscopic level. Figure 7 The left side shows the filtrate before filtration, which is dark red, and the right side shows the filtrate after filtration through the self-cleaning membrane. It can be seen that the transparency of the filtrate after filtration through the self-cleaning membrane is significantly improved, and the overall clarity is basically clear, indicating that the self-cleaning membrane effectively intercepts pollutants and has good filtration performance. The left side of the upper membrane is before filtration, and the right side is after filtration. It can also be seen that the surface turns red and effectively intercepts Oil Red O.
[0113] Example 6
[0114] Step 1, preparing a chelating agent solution, weighing 0.05 mol of ethanolamine and dissolving it in 50 mL of deionized water, stirring with a magnetic stirrer for 30 minutes to obtain a chelating agent solution;
[0115] Step 2, prepare a barium salt solution, weigh 0.05 mol BaCl2 and dissolve it in 50 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless barium salt solution system;
[0116] Step 3, prepare titanium salt solution, weigh 0.042 mol C 16 H 36 O4Ti was dissolved in 50 mL of anhydrous ethanol and stirred for 30 min using a magnetic stirrer to obtain a colorless titanium salt solution system;
[0117] Step 4, prepare an alkaline solution, weigh 0.45 mol KOH and dissolve it in 100 mL deionized water, and stir it with a magnetic stirrer for 30 minutes to obtain a colorless alkaline solution;
[0118] Step 5, prepare a barium titanate precursor solution, slowly add the chelating agent solution and the barium salt solution into the titanium salt solution, use a magnetic stirrer to stir for 30 minutes, stir evenly to form a mixed solution system, then add the alkaline solution to the mixed solution system, and finally react under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, and obtain a BaTiO3 precursor solution.
[0119] Step 6: Prepare a barium zirconate titanate precursor solution, weigh 0.008 mol of tetragonal ZrO2 nanopowder and add it to the BaTiO3 precursor solution, stir it with a magnetic stirrer for 30 minutes, and obtain BaZr x Ti 1-x O3 precursor solution.
[0120] Step 7, Preparation of BaZr x Ti 1-x O3 powder: BaZrx Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, with a water bath temperature of 50°C, a rotary evaporator pressure of 145 mbar, and a time of 30 min; the parameters for the second stage were: water bath temperature of 70°C, rotary evaporator pressure of 72 mbar, and a time of 90 min. The obtained white precipitate was first washed 3 times with ultrapure water, and then washed 3 times with anhydrous ethanol; finally, it was placed in an oven at 80°C and dried for 12 h to obtain BaZr x Ti 1-x O3 precursor powder; the precursor powder is placed in an air furnace and calcined at a high temperature of 1200°C for 4 hours to obtain tetragonal BaZr x Ti 1-x O3 powder;
[0121] Step 8, preparing a film-forming agent solution, weighing 6 g of PEG and dissolving it in 100 mL of deionized water, stirring it with a magnetic stirrer for 10 minutes to obtain a film-forming agent solution.
[0122] Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane: weigh 1g of tetragonal BaZr x Ti 1-x O3 powder was placed in a mortar, and 2 mL of film-forming agent solution was dropped into it. After being ground evenly, it was added into a pressure mold with a diameter of 25 mm. The pressure was 15 MPa and the holding time was 100 s. A tablet press was used to form a ceramic film blank. The obtained ceramic blank was placed in an air furnace for high-temperature calcination at a temperature of 1200 ° C and a holding time of 3 h. After calcination, tetragonal BaZr x Ti 1-x O3 ceramic membrane.
[0123] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0124] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A tetragonal BaZr x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: The specific steps include: Step 1, prepare chelating agent solution Weigh a chelating agent and dissolve it in deionized water, stirring until it is completely dissolved to obtain a chelating agent solution; Step 2: Prepare barium salt solution Weigh BaCl2 and dissolve it in deionized water, stirring until it is completely dissolved to obtain a colorless barium salt solution system; Step 3, prepare titanium salt solution Weigh C 16 H 36 O4Ti was dissolved in anhydrous ethanol and stirred evenly to obtain a colorless titanium salt solution system; Step 4: Prepare alkaline solution Weigh KOH and dissolve it in deionized water and stir evenly until the KOH particles are completely dissolved to obtain a colorless alkaline solution; Step 5: Prepare barium titanate precursor solution Slowly adding the chelating agent solution prepared in step 1 and the barium salt solution prepared in step 2 to the titanium salt solution prepared in step 3, stirring evenly to form a mixed solution system, then adding the alkaline solution prepared in step 4 to the mixed solution system, and finally reacting under alkaline conditions to obtain a turbid liquid system with a colorless upper layer and a white lower layer, thereby obtaining a BaTiO3 precursor solution; Step 6: Prepare barium zirconate titanate precursor solution Add ZrO2 powder to the BaTiO3 precursor solution prepared in step 5 and stir evenly to obtain BaZr x Ti 1-x O3 precursor solution; Step 7, preparation of BaZr x Ti 1-x O3 powder The BaZr prepared in step 6 x Ti 1-x The O3 precursor solution was poured into an eggplant-shaped bottle for rotary evaporation reaction, and the obtained white precipitate was centrifuged and dried to obtain BaZr x Ti 1-x O3 precursor powder; BaZr x Ti 1-x The O3 precursor powder was placed in an air furnace and calcined at high temperature to obtain tetragonal BaZr x Ti 1-x O3 powder; Step 8: Prepare film-forming solution Weigh a film-forming agent and dissolve it in deionized water, stirring evenly to obtain a film-forming agent solution; Step 9, preparation of BaZr x Ti 1-x O3 ceramic self-cleaning membrane Weigh the tetragonal BaZr prepared in step 7 x Ti 1-x O3 powder is placed in a mortar, and the film-forming agent solution prepared in step 8 is dripped into it. After being ground evenly, it is added to a pressure mold, and a tablet press is used to form a ceramic film blank; the obtained ceramic blank is placed in an air furnace for high-temperature calcination to obtain a tetragonal BaZr x Ti 1-x O3 ceramic membrane.
2. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: In step 1, step 2, step 3, step 4, step 5, step 6 and step 8, a magnetic stirrer is used for the stirring process.
3. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: The chelating agent in step 1 is ethanolamine.
4. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: The ZrO2 powder in step 6 is tetragonal nanoparticles.
5. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: The rotary evaporation reaction process in step 7 consists of two stages. The reaction conditions of the first stage are: water bath temperature 50°C-60°C, rotary evaporator pressure 142mbar-146mbar, and time 30min-60min; the reaction conditions of the second stage are: water bath temperature 60°C-70°C, rotary evaporator pressure 72mbar-76mbar, and time 90min-120min; the centrifugation process includes three water washes and three alcohol washes; the drying conditions are: the white precipitate is dried in an oven, the drying temperature is 60°C-100°C, and the drying time is 12h-36h; BaZr x Ti 1-x The high temperature calcination temperature of O3 precursor powder is 800℃-1200℃, and the high temperature calcination time is 1h-4h.
6. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: The film-forming agent in step 8 is any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, propylene glycol, and glycerol.
7. A tetragonal BaZr according to claim 1 x Ti 1-x The method for preparing an O3 ceramic self-cleaning membrane is characterized in that: In step 9, the pressing pressure of the ceramic membrane blank formed by the tablet press is 8Mpa-15Mpa, the holding time is 60s-180s, the high-temperature calcination temperature is 1200℃-1400℃, and the high-temperature calcination time is 1h-4h.
8. A tetragonal BaZr according to any one of claims 1 to 7 x Ti 1-x Preparation method of O3 ceramic self-cleaning membrane prepared by tetragonal BaZr x Ti 1-x O3 ceramic self-cleaning membrane.
Citation Information
Patent Citations
Method for preparing mesoporous barium zirconate titanate ceramic nanoparticles
CN114315349A
Wet chemical prepn process of leadless functional barium titanate ceramic film
CN1350071A
Method for liquid phase synthesis of barium titanate nanopowder
CN1765752A
Composite material and method for producing composite material and its use as capacitor material
EP4112580A1
Ceramic mass, method for the production of a ceramic mass and use of a ceramic mass
US20030109375A1